SISTEM INFORMASI TRACKING UNTUK MENINGKATKAN PELAYANAN JASA PERBAIKAN HANDPHONE BERBASIS ANDROID WEBVIEW - Bayu Purbaya (Informatika Publisher, 2021)
At present, the Citra Ponsel shop in providing mobile phone repair services to service users is still using the conventional system, which is a common method that is commonly used, so that in managing service user data there are still problems, such as delays in providing information to service users and there are queues of users. services that will repair, pick up or just want to know the development of cellphones that are being repaired. There needs to be a tracking information system for android-based cellphone repair services at the Citra Ponsel Store as a means that can help simplify and speed up service users to get the information they need. The method used in developing the information system in this research is Unified Process. With the tracking information system, it is hoped that it can provide convenience and speed up service users in getting information about cellphones that are being repaired, and can improve the quality of repair services at the Citra Ponsel Store.